Quality evaluation of moringa (Moringa oleifera) leaves fermented by various dosages of Aspergillus niger as ingredients for fish feeds. Issue 1 (1st December 2022) - Suharman, I; Aryani, N; Hasan, B; Adelina, A; Lukistyowati, I; Raysha, L; Karo-Karo, R M; Caipang, C M A
Abstract: The Moringa oleifera leaves are a promising candidate plant protein source for fish feeds because of its high crude protein content, varying from 21% to 32%. However, because of high content of crude fiber in moringa, it can reduce the digestibiliy of the nutrients. Therefore, there is a need for intervention to improve the quality of M. oleifera leaves. The current research was carried out to assess the nutrient quality of M. oleifera leaf meal (MOLM) following fermentation with Aspergillus niger at different dosages as alternative feed ingredients for fish. In this study, a completely randomized design with four treatments and three repetitions was used. The treatments were as folllows: F0 = Fermentation of MOLM without A. niger (control), F1 = Fermentation of MOLM with A. niger at 2% (w/w) of MOLM, F2 = Fermentation of MOLM with A. niger at 4% (w/w) of MOLM and F3 = Fermentation of MOLM with A. niger at 6% (w/w) of MOLM. Results showed that MOLM fermented with A. niger had a significant effect on crude fiber and crude protein. It can be concluded that MOLM supplemented with 6% A. niger could improve crude protein and crude fiber quality of Moringa oleifera leaves.